1988
DOI: 10.1107/s0108768188004173
|View full text |Cite
|
Sign up to set email alerts
|

Commensurately modulated structure of thiourea at 170 K

Abstract: The ninefold superstructure of SC(NHz) 2 was determined by single-crystal X-ray diffractometry at 170 K; orthorhombic, Pbnm, a = 5.467 (1), b = 7.545 (1), c=76.867(I1) A, V=3171.1A 3, Z=36, Dx= 1.435 Mg m -3, Cu K~t, 2 = 1.5418 A, ~ = 5.89 mm-', R=0.048 for 1510 independent reflections. The commensurate phase is stable between the ferroelectric phase (I) and the incommensurate phase (II), in a temperature range of about 2 K. The structure is characterized by a rotation of the SC(NH2) 2 molecule along the c axi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…Summary of the mode decomposition of the threefold lock-in phase of K 2 SeO 4 (Yamada et al, 1984). , 1989) and as a conventional superstructure (Tanisaki et al, 1988). The two models were shown to be approximately equivalent (Perez-Mato, 1991) (see below).…”
Section: Table 16mentioning
confidence: 99%
See 1 more Smart Citation
“…Summary of the mode decomposition of the threefold lock-in phase of K 2 SeO 4 (Yamada et al, 1984). , 1989) and as a conventional superstructure (Tanisaki et al, 1988). The two models were shown to be approximately equivalent (Perez-Mato, 1991) (see below).…”
Section: Table 16mentioning
confidence: 99%
“…Table 18 shows the polarization vector of the primary DT4 distortion in the mode description. The sinusoidal function so defined, together with the modulation wavevector, is sufficient to describe the displacements of the equivalent atoms in the nine Table 18 Reference structure and polarization vector of the (0, 1/9, 0) DT4 distortion in the ninefold Pnma phase of thiourea according to the structure reported as model 1 of Tanisaki et al (1988) Table 17 Summary of the mode decomposition of the ninefold phase of thiourea according to the structure reported as model 1 in Tanisaki et al (1988) (H atoms not included). The three cations S, C and N have a single independent site in the parent unit cell and are split into five, five and nine independent sites, respectively, in the ninefold structure.…”
Section: Table 16mentioning
confidence: 99%
“…The structure of the modulated phases has been studied by many workers (Shiozaki, 1971;McKenzie 1975;Takahashi, Onodera & Shiozaki, 1987Gao, Gajhede, Mallinson, Petricek & Coppens, 1988;Tanisaki, Mashiyama & Hasebe, 1988;Simonson, D6noyer, Currat & Vettier, 1988;Zufiiga, Madariaga, Paciorek, P6rez-Mato, Ezpeleta & Etxebarria, 1989). In the works of McKenzie (1975), Takahashi et al (1987Takahashi et al ( , 1988, Gao et al (1988) and Simonson et al (1988), the molecule of thiourea is 0108-7681/90/050661-04503.00…”
Section: Introductionmentioning
confidence: 99%
“…the same value of ns). Such strict regularity is not exactly true: Among the six modulation functions obtained in a rigid-body approximation of the molecule, there is one that remains almost sinusoidal, the one corresponding to the translation along the a axis (Zfifiiga et al, 1989;Tanisaki, Mashiyama & Hasebe, 1988). The reason for this exception is well understood (Aramburu, Madariaga & Perez-Mato, 1994) but for simplicity this feature has been neglected in the calculations above.…”
Section: Time Relaxation Of the Soliton Densitymentioning
confidence: 99%
“…It will be shown that the time evolution of the reflections can be fully explained in terms of a certain variation of the form of the structural modulation. The previous knowledge of the incommensurate structure determined (Zfifiiga et al, 1989;.Tanisaki, Mashiyama & Hasebe, 1988) and the assumption that the structural modulation approximately satisfies the sine-Gordon equation (Aramburu, Madariaga & Prrez-Mato, 1994, 1995 has been essential for a successful quantitative analysis of the results. The present study demonstrates that, when properly chosen and analysed, check reflections can provide a direct insight of the time relaxation of IC modulations.…”
Section: Introductionmentioning
confidence: 99%